Information Diffusion in Computer Science Citation Networks - Shi, Xiaolin; Tseng, Belle; Adamic, Lada (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
The paper citation network is a traditional social medium for the exchange of ideas and knowledge. In this paper we examine information diffusion in citation networks by analyzing the correlations between various citation choices and the subsequent impact of the articles. We find that citing recent papers and papers within the same scholarly community garners a slightly larger number of citations on average. However, this correlation is weaker among well-cited papers implying that for high impact work citing within one's field is of lesser importance.